Local Activation of the Alternative Pathway of Complement System in Mycotic Keratitis Patient Tear - Shait Mohammed, Mohammed Razeeth; Krishnan, Sandhya; Amrathlal, Rabbind Singh; Jayapal, Jeya Maheshwari; Namperumalsamy, Venkatesh Prajna; Prajna, Lalitha; Kuppamuthu, Dharmalingam (Frontiers in Cellular and Infection Microbiology, 2020)
Aspergillus flavus and Fusarium solani are the predominant causative agents of mycotic keratitis in the tropical part of the world. Tear proteins play a major role in the innate immune response against these fungal infections as has been shown by the presence of complement proteins and neutrophil extracellular trap proteins in keratitis patients tear. In this study, we established the presence of the components of the alternate pathway of complement system and their functional state in the tear film of mycotic keratitis patients. The complement proteins namely, C3 and CFH were found only in the open-eye tear of patients but not in control individuals. In vitro analysis showed binding of purified C3b and CFH to fungal spores, which confirmed that the spores can provide a foreign surface for forming the complement complex. Analysis of spore bound tear proteins by mass spectrometry exhibited the presence of known proteins of the alternate pathway complement cascade in keratitis patient tear. Hemolytic assay using rabbit RBC confirmed the presence of a functional alternate pathway of complement cascade in the tear proteome of the patients. The presence of negative regulators, CFH and CFI, in the patient tear indicate that the complement activity is tightly regulated during fungal infection. Mass spectrometry data show vitronectin and clusterin, two known inhibitors of the membrane attack complex only in the patient tear. These data demonstrate the activation of the alternate pathway of complement cascade during the early stages of infection. Interestingly, the production of multiple negative regulators of complement cascade implies the pathogen can effectively evade the host complement system during infection.